How do you solve √6(2√3-4√2)

√6(2√3 - 4√2)

= √6(2√3) - √6(4√2) {used distributive property}

= 2√18 - 4√12 {multiplied through}

= 2√9√2 - 4√4√3 {broke down square roots of 18 and 12}

= 2(3)√2 - 4(2)√3 {found square roots of 9 and 4}

= 6√2 - 8√3 {multiplied through}

- Algebra House

= √6(2√3) - √6(4√2) {used distributive property}

= 2√18 - 4√12 {multiplied through}

= 2√9√2 - 4√4√3 {broke down square roots of 18 and 12}

= 2(3)√2 - 4(2)√3 {found square roots of 9 and 4}

= 6√2 - 8√3 {multiplied through}

- Algebra House